Hubungan Konsep Diri Terhadap Perilaku Konsumtif Pada Siswa SMA Teratai Putih Global Bekasi - Nabila Putri Alia Ramadhani; Andreas Corsini Widya Nugraha (Global Sustainability Research Institute, 2024)
Introduction: This research aims to determine the relationship between self-concept and consumer behavior. Self-concept is the basis for the formationof behavior.Methods: This research uses quantitative methods, namely using linear teststudies and cholera tests. The population that researchers used for researchwere students at Teratai Putih Global High School, Bekasi. Sampling usesquantitative techniques. This research has 199 respondents who will be usedby researchers.Results: Based on the Spearman rho correlation analysis, a correlationcoefficient value of 0.161 was obtained, this value refers to there is norelationship between self-concept and consumer behavior. A negative valueindicates that the lower the self-concept, the lower the consumptivebehavior, and vice versa, the lower the consumptive behavior, the lower theself-concept. Students with consumer behavior tend to have a poor level ofself-concept because they only follow trends and influences on thesurrounding environment. Furthermore, it was found that consumer behaviorplayed a role in influencing 93.3% of the self-concept of students at TerataiPutih Global High School, Bekasi.Conclusion and suggestion: Conclusions and suggestions: States that thealternative hypothesis (ha) is rejected. The lower the self-concept, the lowerthe consumptive behavior, and the lower the consumptive behavior, the lowerthe self-concept.